Una aproximación a un estado del arte de la educación energética - Castro M., John E. (Revista Científica, 2011)
In this article one first approach to a state-of-the-art becomes on education energetic which is part of the titled doctoral thesis: The education energetic in the public Universities of Bogota. Initially they appear some antecedent on education energetic, later is realized the one first planning from three aspects: the object of the education energetic, its logic and its objectives. Finally, a balance becomes of how the education has been treated energetic on the part of the scientific education.